Meta-analysis of risk factors for postoperative lower extremity deep vein thrombosis in patients with gynecologic malignancies - Gong, Danzhu; Wang, Qi (Frontiers in Surgery, 2025)
IntroductionThis study aims to elucidate the risk factors associated with postoperative lower extremity deep vein thrombosis (DVT) in patients afflicted with gynecologic malignancies.MethodsA comprehensive search was conducted across CNKI, CQVIP, Wanfang, and PubMed databases for literature published from January 1, 2024, concerning the risk factors for postoperative DVT in patients with gynecologic cancers. Two researchers independently and objectively screened, extracted, and evaluated the pertinent data. Subsequently, the extracted data were subjected to meta-analysis using STATA software.ResultsA total of twelve studies fulfilling the inclusion criteria were analyzed, encompassing 2,553 cases. The meta-analysis revealed that significant risk factors for postoperative lower extremity DVT in patients with gynecologic malignancies include age [Odds Ratio (OR) = 1.35, 95% Confidence Interval (CI) (1.19, 1.54), P < 0.001], Body Mass Index (BMI) [OR = 1.67, 95% CI (1.05, 2.66), P < 0.001], plasma D-dimer levels [OR = 3.39, 95% CI (1.24, 9.24), P < 0.001], duration of surgery [OR = 2.24, 95% CI (1.24, 4.01), P < 0.001], and duration of postoperative bed rest [OR = 2.14, 95% CI (1.56, 2.94), P < 0.001].DiscussionThe study identifies multiple risk factors influencing the incidence of postoperative lower extremity DVT in patients with gynecologic malignancies. Notably, age, BMI, plasma D-dimer levels, surgical duration, and postoperative bed rest emerge as significant predictors. These findings underscore the necessity for targeted prophylaxis and therapeutic interventions in the clinical management of such patients.